Progress in Carbon Dioxide Capture and Storage (CCS) and Conversion Utilization Research - Ye Junteng (E3S Web of Conferences)
The issue of climate change caused by excessive carbon dioxide (CO2) emissions has garnered widespread attention. This paper reviews the current major technologies for CO2 treatment, including carbon capture and storage (CCS) and CO2 utilization. CCS technology effectively reduces atmospheric CO2 concentrations by injecting captured CO2 underground for long-term storage, thereby mitigating climate change. Additionally, improvements in technology can enhance oil recovery rates. CO2 utilization transforms CO2 into high-value chemicals such as methane and carbon monoxide (CO) through thermal catalysis, photocatalysis, and electrocatalysis. Despite challenges such as low energy efficiency and high costs, these technologies show significant potential in reducing carbon emissions and promoting carbon recycling.